Responsible management education for a sustainable world. Issue 1 (9th February 2015) - Eric Cornuel, Dr; Ulrich Hommel, Professor; Dyllick, Thomas
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The reforms in business schools based on the Ford and Carnegie Foundation reports (Pierson, 1959; Gordon and Howell, 1959) have been very successful in embedding management in a research-based body of knowledge, thereby elevating the academic status of business administration. These reforms, however, did nothing toward making management more socially trustworthy or management education more responsible. In the light of the pressing economic, social and environmental crises the world is facing, the feeling is spreading that not only business and economics but business schools also need to change fundamentally, if they want to be a provider of solutions to these crises and thereby keep and regain their legitimacy. The purpose of this paper is to provide a critical analysis of the fundamental challenges facing the role of business schools and their contributions in the areas of education, research, managing faculty, and role of the business school. It presents suggestions what responsible management education for a sustainable world could and should look like. Design/methodology/approach – The paper builds on the existing literature on the needed changes in business schools and has been written as part of a large international project, the 50+20 initiative (www.50plus20.org), which was developed by a broad coalition of organizations with the World Business School Council for Sustainable Business (WBSCSB), the Globally Responsible Leadership Initiative (GRLI) and the UN Principles for Responsible Management Education (PRME) at its core and 16 business schools and organizations from all around the world as supporters (Muff et al., 2013). Findings – Business schools need to transform themselves fundamentally, if they want to be a provider of solutions to the crises of responsibility and sustainability and thereby keep and regain their legitimacy. Originality/value – The paper pulls together insights from a diverse area of literature and develops practical conclusions.